Cerebrocerebellar functional connectivity in reading networks for bilinguals - Chua, Serena Wei Ting (Nanyang Technological University, 2023)
Evidence from neuroimaging studies have consistently found that the sub-lexical route of reading (grapheme-to-phoneme mapping) corresponded to a dorsal stream of cerebral regions. Conversely, the lexical route (retrieval of sound forms from whole words) corresponded to a more ventral network of cerebral regions. Less is known about the relationship between cerebro-cerebellar connections and reading-related processes. Thus, to map cerebro-cerebellar functional connectivity networks to a lexical or a sub-lexical route, the current study examined functional magnetic resonance imaging (fMRI) data collected from 32 Chinese-English and 33 Tamil-English bilingual adults. These participants silently read words, pseudowords, and nonwords in English and their mother tongue in a 3T Siemens Prisma scanner. Linear Mixed effects modelling was used to examine functional connectivity matrices from Region-of-Interest (ROI)-to-ROI connections. The results revealed significant functional connectivity between the left fusiform gyrus (FFG) and the right R6 sub-region of lobule VI when reading English nonwords (vs. English words) and when reading Tamil pseudowords (vs. Tamil words). When reading English, there was greater functional connectivity between the left inferior parietal lobule and pars opercularis of the left inferior frontal gyrus (vs. Chinese). Reading Tamil nonwords involved higher connectivity between the right lobule VIIB region and the right R2 sub-region of lobule VI (vs. English nonwords). These findings provided compelling evidence for the involvement of the left FFG-right R6 involvement in the sub-lexical processes of reading. Additionally, they highlight the need to further clarify cerebro-cerebellar involvement in reading-related processes.